Web 2.0 tools in facilitating the construction of knowledge in higher education / Zati Atiqah Mohamad Tanuri, Nor Azlina Azmi and Mohd Zool Hilmie Mohamad Sawal - Mohamad Tanuri, Zati Atiqah; Azmi, Nor Azlina; Mohamad Sawal, Mohd Zool Hilmie (Universiti Teknologi MARA, Pulau Pinang, 2014)
The development of Web 2.0 technologies creates new methods in the learning process. The adaptation of Web 2.0 as a learning tool is due to the familiarity of the use of Web 2.0 technologies by students. This study attempts to observe the usage of Web 2.0 for knowledge construction in the learning process. The objectives of the study are to identify the use of Web 2.0 tools which contribute to the construction of knowledge, and to identify which categories of Web 2.0 tools are mostly used by the students. This research used the questionnaire survey method. A total of 397 questionnaires were distributed among the students of private higher education institutions. Based on the findings, the use of Web 2.0 tools contributed to the knowledge in terms of facilitating communication and collaboration from different teams, accessing knowledge such as online subject communities, experts and other educators, using lesson videos and online clips and lastly students used Web 2.0 tools to share similar interests and create communities around a centre of interest. Thus, the use of Web 2.0 tools is a trend among students whereby they can communicate comfortably among their peers and get access easily to knowledge which facilitate them in their learning environment.